Improved force fields for the simulation of biological systems - Suh, Kyung-Shin (Kansas State University, 2023)
Computer simulation is a common tool used to investigate the behavior of a wide variety of systems. The accuracy, and therefore the usefulness, of a simulation is largely dependent on the quality of the underlying force field (FF) used to model the interactions between atoms and molecules. Therefore, it is essential to validate the capacity of any FF to accurately depict the properties of the system under study. Various studies have identified problems with excessive solute aggregation in solutions, especially for intrinsically disordered proteins/peptides (IDP), when using traditional FFs. Here, we use an established approach for developing new improved FFs for the simulation of solutions of biological interest. The Kirkwood-Buff (KB) Force Field approach was developed to compare experimentally derived KB integrals with those provided by molecular dynamic simulations. Here we examine a variety of intermolecular interactions in aqueous solutions, together with the behavior of peptides at various interfaces, using KB theory and molecular simulations. First, we describe force fields for the simulation of charged and neutral zwitterionic amino acids, sulfates, alkyl sulfates, and sodium dodecyl sulfate (SDS) in aqueous solution, that are specifically developed to reproduce the KB Integrals derived from experimental data. Additional studies of selected small peptides both in the presence and absence of SDS micelles using these new FFs provided conformational changes dependent on the presence of SDS micelles and in agreement with experiment. Further studies of Amylin, an IDP, at various interfaces such as air/water, water/micelle, and lipid/water, also suggested significant conformational changes. Again, the application of these new FFs for studying interface behavior yielded results in good agreement with experimental data.
Keywords: Force field; KBFF; Amino acid; SDS; Amylin; Interface